Towards precision medicine in ANCA-associated vasculitis. (17th October 2017) - van der Geest, Kornelis S M; Brouwer, Elisabeth; Sanders, Jan-Stephan; Sandovici, Maria; Bos, Nicolaas A; Boots, Annemieke M H; Abdulahad, Wayel H; Stegeman, Coen A; Kallenberg, Cees G M; Heeringa, Peter; Rutgers, Abraham
Abstract: ANCA-associated vasculitis (AAV) is characterized by inflammation and destruction of small and medium-sized vessels. Current management strategies for AAV have been validated in large groups of patients. However, recent insights indicate that distinct patient subsets may actually exist within AAV, thereby justifying the development of more personalized treatment strategies. In this review, we discuss current evidence for a better classification of AAV based on ANCA type. We describe how thus defined categories of AAV patients may differ in genetic background, clinical presentation, immune pathology, response to treatment and disease outcome. We also explore how these insights may provide a rationale for targeted treatments in different categories of AAV patients. Finally, we provide recommendations on how to further establish precision medicine in AAV.